Bio-bibliography of meritorious men and women of the homeland and citizens of honour 1847-2008 - Delgado Quirós, Orlando (2010)
Today's society, called the information society, grows rapidly and undergoes changes in the sources of information due to Information and Communication Technologies ("Tics"), in view of this situation it is necessary to create instruments or reference sources that allow the user the accessibility and use of information. The general objective of this research work was to produce a printed and digital reference work, which will compile each of the biographies and works written by the Beneméritos(as) of the Homeland and Honorary Citizens and thus facilitate access to information and strengthen the work of dissemination carried out by the "Víctor Manuel Sanabria Martínez" Library of the Legislative Assembly, through its publications, exhibitions and related activities, to publicize their documentary collections.